Implementasi Metode Writing-To-Learn sebagai Upaya Mengintegrasikan Literasi Ekologis dalam Penulisan Makalah Mahasiswa: Sebuah Studi Kualitatif - Hera Septriana; Onok Yayang Pamungkas; Shelia Anjarani (Ruang Kata, 2026)
The implementation of the Writing-to-Learn method is an effort to integrate ecological literacy in student paper writing. This research uses a qualitative approach with a descriptive design, involving students of the Indonesian Language and Literature Education study program who take the Writing Scientific Papers course. Data was obtained through observation, document analysis, and in-depth interviews. The analysis was carried out in the stages of data reduction, data presentation, and conclusion drawn. The results of the study show that the application of the Writing-to-Learn method effectively increases students' ecological awareness, both from cognitive aspects (environmental knowledge), affective (concern and attitude), and behavior (real actions towards the environment). The average increase in these three aspects reached 0.8 points or equivalent to 28.8%. In addition, the quality of student paper writing also improved with an average overall score of 3.65 in the excellent category, especially in the aspects of writing structure, depth of analysis of ecological issues, and accuracy in the use of scientific language. These findings confirm that the Writing-to-Learn method not only functions as a writing learning strategy, but also as a means of internalizing ecological values that foster environmental awareness and responsibility in students. The integration of ecological literacy through scientific writing activities is a strategic step in realizing continuous education in higher education. Keywords: Writing-to-Learn, ecological literacy, education